Characterization of hypersensitivity reactions reported among Andrographis paniculata users in Thailand using Health Product Vigilance Center (HPVC) database - Suwankesawong W. (BioMed Central, 2015)
© 2014 Suwankesawong et al.; licensee BioMed Central. Background: Andrographis paniculata (andrographis) is one of the herbal products that are widely used for various indications. Hypersensitivity reactions have been reported among subjects receiving Andrographis paniculata in Thailand. Understanding of characteristics of patients, adverse events, and clinical outcomes is essential for ensuring population safety. Methods: Thai Vigibase data from February 2001 to December 2012 involving andrographis products were used. This database includes the reports submitted through the spontaneous reporting system and intensive monitoring programmes. The database contained patient characteristic, adverse events associated with andrographis products, and details on seriousness, causality, and clinical outcomes. Case reports were included for final analysis if they met the inclusion criteria; 1) reports with andrographis being the only suspected cause, 2) reports with terms consistent with the constellation of hypersensitivity reactions, and 3) reports with terms considered critical terms according to WHO criteria. Descriptive statistics were used. Results: A total of 248 case reports of andrographis-associated adverse events were identified. Only 106 case reports specified andrographis herbal product as the only suspected drug and reported at least one term consistent with constellation of hypersensitivity reactions. Conclusions: Our findings suggested that hypersensitivity reactions have been reported among patients receiving Andrographis paniculata. Healthcare professionals should be aware of this potential risk. Further investigation of the causal relationship is needed; meanwhile including hypersensitivity reactions for andrographis product labeling should be considered.